Implikasi dan Tata Kelola Digitalisasi Pengawasan Kepatuhan Hukum Pada Anak Perusahaan Badan Usaha Milik Negara (AP BUMN) (Studi Pada PT Indonesia Chemical Alumina) - Haris Sanjaya; Radian Salman; Arif Rahman Hakim (Fakultas Hukum, Universitas Warmadewa, 2026)
This research examines the implementation of the ICA Compliance Management System (ICA CMS Application) at PT Indonesia Chemical Alumina (ICA) as a digital innovation to manage increasingly complex legal compliance. Problems arising from manual monitoring systems cause inefficiencies, data errors, and a lack of transparency. The ICA CMS Application, developed internally, aims to optimize integrated and real-time compliance data management, enhance the efficiency of validation, verification, and reporting of legal compliance. This study employs a qualitative method with a socio-legal approach to analyze the multidimensional impact of digitalization on legal compliance oversight, the digitalization of paper-based workflows, and intellectual property protection for the application developed within the company. The results are expected to provide strategic recommendations for the development of digital-based compliance systems at ICA and other companies, shifting the paradigm from reactive compliance to proactive compliance in addressing industry regulatory dynamics.